Swamplands productivity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
international seminar in Antananarivo, Madagascar, in December 1991 on the subject of 'Swamplands and rice-growing' 00394026;SE039/14;;E;Bookshelf;;Fruit and two veg ;'fruit production; vegetable production